Construção do conhecimento e a reafirmação do território: a contribuição da Turma Margarida Maria Alves, do Curso de Ciências Agrárias, Programa Nacional de Educação na Reforma Agrária - Lorenzo, Ivanalda Dantas Nobrega Di (2013)
This thesis aimed to identify the contributions of the Class Margarida Maria Alves, Course of Agricultural Sciences Program Student Agreement / Social Movements Field (PEC / MSC), Federal University of Paraíba (UFPB), Campus III, municipality of Bananeiras - PB, located in Paraíba arid mesoregion. Reflected about public policy for the field, especially the Education Field, resulting from a research project related to the Observatory for Education, called Higher Education in Brazil (2000-2008): an interdisciplinary analysis of policies for the development of the field Brazil, in which one tries to analyze courses linked to the National Education Program in Agrarian Reform (PRONERA). From this, we developed a reflection on Rural Education, focusing on higher education and in the area of Agricultural Sciences, based on the methodology of the Pedagogy of Alternation, as elements inherent in the struggle for human rights in the country and its confrontations with the model prevailing economic, whose bases reveal the cultural uprooting peasants. Referenced on the Marxist studies for which the production of material life is mediated by social relations of production and the productive forces, determining the mode of living, thinking and transmitting knowledge, which humans have, in reality, where live. Following this thought, education in this country, and with her teaching, are determined by the development of production of material life, meeting the expectations of current economic system, whose hegemonic forces, the state and the major owners of the means of production, defined in favor of what and who is studying what and what is studied. Showed up considerations concerning the construction of the territory peasant front development of Higher Education, through PRONERA. The study was based on documents of the Movement For a Rural Education in the Course Project, the legal order of Field Education and literature. A thesis submitted four chapters beyond considerations: 1 - Introduction, stating the trajectory of Researcher and research methodology; 2 - Theoretical about the territories of the peasantry and agrarian development policies of the country, among them, the policies of reform land, technical assistance and Education Field 3 - PRONERA and the Course of Agricultural Sciences, in reference to Class Margarida Maria Alves, with emphasis on building partnerships, training parallel, dual training and Political Pedagogical Project (PPP) 4 - The movement of alternating pedagogy pedagogy of the movement and organic domestic produced in living together students, beyond the approach on the period of professional practice. The research subjects are the Professionals Graduates Course, plus UFPB teachers, representatives of the National Institute of Colonization and Agrarian Reform (INCRA-PB), Social Movements Field (MSC) and the Fundação José Américo (FJA). The time frame is set between the years 2004 to 2012, including the times of formation and professional. The analysis method, dialectical historical materialism was accompanied by appropriate methodology to the reality of respondents, among them the literature, field and documentary, with semistructured interviews, individual and collective, quizzes, oral history, content analysis, notes in field notebook and systematic observation. The results stated that the production of academic knowledge, while legitimizing the existing order, it was found that the conflicts and contradictions that exist in the implementation of the course, from the practices students, teachers and those responsible for running the course, produced a pedagogical movement collectively organized, able to transform the mode of producing knowledge and reaffirm the territory farmer, from a basic humanistic education.